Validation of the T descriptor in the new 8th TNM classification for non-small cell lung cancer - Jung, Hee Suk; Lee, Jin Gu; Lee, Chang Young; Kim, Dae Joon; Chung, Kyung Young (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Background: To validate new proposals for the revision of T descriptors and to compare the prognostic value of the seventh and forthcoming eighth edition of the tumor, node and metastasis (TNM) classification for lung cancer. Methods: A retrospective analysis was conducted of 1,316 patients with non-small lung cancer who underwent pulmonary resection between 1999 and 2012. Patients who had a positive nodal status or distant metastasis were excluded. We classified these patients according to the seventh and eighth edition of the TNM system, and analyzed differences in stage specific survival. Harrell’s concordance (C)-index and Heagerty’s integrated area under the curve (iAUC) were used to assess the overall predictive ability of the different TNM versions. Results: There were no significant survival differences between each stage based on the T stage criteria of the eighth edition, most notably between T1a and T1b (P=0.752), and T1c, T2a, and T2b (P=0.832). The C-indices of the classification based on the seventh and eighth edition were 0.681 and 0.675, respectively. There was no significant difference in the C-indices between the seventh and eighth edition. The iAUC value for overall survival of the seventh and eighth staging editions was 0.637 and 0.631, respectively. The differences in iAUC between the seventh and eighth editions were also not statistically significant. Conclusions: The newly proposed T descriptors in the eighth TNM classification system did not allow a more accurate prediction of prognosis compared with the current seventh edition in our population.